Disability-adjusted life years for severe acute malnutrition: implications of alternative model specifications. Issue 15 (3rd July 2019) - Puett, Chloe; Bulti, Assaye; Myatt, Mark
Abstract: Objective: Reducing the burden of childhood severe acute malnutrition (SAM) is key to improving global child health outcomes. Assessing cost-effectiveness of nutrition interventions remains an important evidence gap. Disability-adjusted life years (DALYs) are a common indicator used in cost-effectiveness analyses. DALYs were established by the Global Burden of Disease (GBD) study. Recent iterations of the GBD have changed the methods used to calculate DALYs by dropping age-weighting and discounting (AD) and updating disability weights (DW). Cost-effectiveness analyses may use either local or international standard life expectancies (LE). Changes in model specifications for calculating DALYs may have implications for cost-effectiveness analyses using DALYs, interpreting historical DALY estimates, and related resource allocation decisions. The present study aimed to quantify the magnitude of change in estimates of DALYs attributable to SAM given recent methodological changes. Design: From secondary data analysis, using parameter values from routine programme monitoring data for two SAM treatment programmes and published literature, eight calculation models were created to estimate DALYs with and without AD, using different sets of DW, and local v . standard LE. Results: Different DW had a marginal effect on DALY estimates. Different LE had a small effect when AD was used, but a large effect when AD was not used. Conclusions: DALY estimates are sensitive to the model used. This complicates comparisons between studies using different models and needs to be accounted for in decision making. It seems sensible for analyses to report results using models with and without AD and using local and standard LE.